Strategi Peningkatan Mutu Pembelajaran pada Sekolah Berbasis Islam di Sekolah Dasar Islam Terpadu Al Ibrohimi Manyar Gresik - Ambar Bella Utami (University of Nahdlatul Ulama Pasuruan, 2021)
Learning has a very important role in improving the quality of education, with quality learning it will produce quality education. This research is more focused on strategies to improve the quality of learning in Islamic-based schools. Because the use of learning strategies can facilitate the learning process, so that optimal learning outcomes are obtained. Without a clear strategy, the process of improving the quality of learning will not be directed so that the learning objectives that have been set cannot be achieved optimally. Strategy improving the quality of learning for teachers can be used as a reference for systematic and measurable action in an effort to improve the quality of learning. For students the use of strategies can facilitate the learning process so as to improve the quality of learning. This study uses a type of field research (field research) using a qualitative descriptive approach. Data collection techniques using documentation, interviews and observations.